Meningkatkan Hasil Belajar Siswa Pada Materi Perbandingan Trigonometri Pada Segitiga Siku-Siku Menggunakan Media Edukatif Pada Kurikulum Merdeka - Susanti, Susanti; Nurdayani, Asri; Raini, Yeni; Paranita, Suzana (Universitas Muhammadiyah Palembang, 2024)
Trigonometry material is very important in mathematics learning because it become one aspects that needs to be trained and developed. The activity using Macromedia Flash can help students develop reasoning, make conjectures and tests ideas in solving problems. Reality, most of students face difficulties of comparison of right triangle Trigonometry as well as. Besides that ,learning process rarely give students opportunity to build their knowledge as suitable as their own cognitive development. The aim of this reserch is action research can help students to understand of comparison of right triangle Trigonometry with Macromedia Flash giving students opportunity to build their own knowledge in high school. The research method which used classroom action research and the research subjects were of X class of SMA Plus Negeri 17 Palembang, South Sumatera. The results of the research obtained learning method can help students to understand right triangle Trigonometry. Start with combination material of Macromedia Flash as starting point, independently and/or interacting with other learning sources such as books, peers, class discussions and teacher reinforcement, students find out comparison of right triangle Trigonometry. The learning results show that by using Macromedia Flash material of comparison of right triangle Trigonometry is easy for students to understand and comprehend